La récupération des déchets à Buenos Aires : un travail de l’âge global - Marie-Noëlle Carré (Confins)
Waste Picking in Buenos Aires : Working in the Global Age - In Buenos Aires (Argentine), waste picking revealed new socio-economical and working dynamics strongly linked with metropolization processes in the years 1990. Since the crisis of 2001, this activity embedded itself in the metropolitan territories, conveying a series of interrogations. From the hypothesis of waste picking as a work of the global age, the article aims at identifying the characteristics of the activity as well as the difficulties the metropolitan actors find in strengthening it inside the existing politico-administrative frame. As a matter of fact, both its instability and innovation root into local territories and global economic and informational networks, which allows us to speak of a hybrid activity. In those conditions, its embeddedness in metropolitan dynamics scrambles the dichotomy between globalization “from upside” and “downside” that is usually called in in order to distinguish the formal and informal circuits. Waste picking in the XXIth century was born from External Direct Investments concentration, from the increasing socio-economical contrasts and the morphological transformations in Buenos Aires, but also from its capillarity and informality. Waste pickers and urban decision-makers are led to invent new arrangements in order to take into account the new social, economic, environmental and territorial stakes of the activity. The most interesting expression of this process is the emergence of recyclable waste selection as an exclusive and first class service for the metropolitan territories more than a basic service for the whole agglomeration.